Perubahan Sistem Konvensional Menjadi Sistem Digitalisasi Bagi UMKM Kebumen di Bidang Konveksi (Studi Kasus Tonight Sablon) - Galih Mahardika Munandar (Universitas Muhammadiyah Gresik, 2022)
MSMEs are starting to move to the digitization system, which was originally a conventional system, but what is still not focused on is the convection sector. There have been many digitalization systems, but they are only focused on digital marketing, not on internal systems that can have an external impact, such as on customers. UMKM Tonight Sablon has many root causes where digital marketing rarely runs, it is still strong in word of mouth with a semi-online system, using only the communication part using Whatsapp. The purpose of this study is to look at the readiness of convection SMEs, especially Tonight Screen Printing, to change the system to digitalization based on the root causes and consumer responses which are through quantitative and qualitative methods. Interview techniques and distributing questionnaires in data collection and there is a statistical classic test to see the validity of the data obtained. The results obtained are consumers asking for changes to the digitization system to make it easier to order and transact and MSMEs can store data using internet of things technology. Websites, mobile applications, Point of Sales (POS), as well as technology on websites such as live chat, cost estimates, and uploading designs can be applied easily, this is the system needed by consumers and business owners of Tonight Sablon.